2019
DOI: 10.3389/fchem.2019.00814
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Synthesis, Characterization and Biological Activities of Ferrocenyl Chalcones and Their QSAR Analysis

Abstract: A new microwave method (MM) has been developed for the synthesis of a series of 16 substituted ferrocenyl chalcones using acetylferrocene (1) with different aldehydes (2a-2p) and comparing it with conventional method (CM). The synthesized compounds were characterized by various spectroscopic techniques viz IR, HR-MS, 1H NMR, and 13C NMR. The time required for completion of reaction in MM varied from 1 to 5 min as compared to CM which required 10–40 h. All the synthesized compounds were screened for antifungal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…9−12 Recently, it has been reported that chalcones have been served as novel insecticides to control insect population, such as angular benzofuran chalcones, 13 chemically modified chalcones, 14 the chalcone derivatives kanakugiol, hydroxychalcone and cardamonin, 15 and furan-chalcones. 16 Moreover, the fungistatic and fungicidal effects of chalcones have also been investigated against phytopathogens in greater detail, including geranyl chalcones, 17 chalcone-based strobilurins, 18 dihydrochalcones (mainly phloridzin, sieboldin, trilobatin, and phloretin), 19 vanillin-chalcones, 20 ferrocenyl-chalcones, 21 isobavachalcones, 22 dihydrochromane-chalcones, 23 and isobavachalcones. 24 In contrast, the herbicidal activity of chalcones has been less investigated.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9−12 Recently, it has been reported that chalcones have been served as novel insecticides to control insect population, such as angular benzofuran chalcones, 13 chemically modified chalcones, 14 the chalcone derivatives kanakugiol, hydroxychalcone and cardamonin, 15 and furan-chalcones. 16 Moreover, the fungistatic and fungicidal effects of chalcones have also been investigated against phytopathogens in greater detail, including geranyl chalcones, 17 chalcone-based strobilurins, 18 dihydrochalcones (mainly phloridzin, sieboldin, trilobatin, and phloretin), 19 vanillin-chalcones, 20 ferrocenyl-chalcones, 21 isobavachalcones, 22 dihydrochromane-chalcones, 23 and isobavachalcones. 24 In contrast, the herbicidal activity of chalcones has been less investigated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These compounds or chalcone-rich plant extracts have competed for substantial research attention as drugs or food preservatives for decades. , Chalcones exhibit numerous interesting biological activities such as anti-cancer, anti-inflammatory, anti-hypertensive, anti-oxidant, anti-viral, anti-bacterial, and anti-microbial activities, which were several times reviewed. Recently, it has been reported that chalcones have been served as novel insecticides to control insect population, such as angular benzofuran chalcones, chemically modified chalcones, the chalcone derivatives kanakugiol, hydroxychalcone and cardamonin, and furan-chalcones . Moreover, the fungistatic and fungicidal effects of chalcones have also been investigated against phytopathogens in greater detail, including geranyl chalcones, chalcone-based strobilurins, dihydrochalcones (mainly phloridzin, sieboldin, trilobatin, and phloretin), vanillin-chalcones, ferrocenyl-chalcones, isobavachalcones, dihydrochromane-chalcones, and isobavachalcones . In contrast, the herbicidal activity of chalcones has been less investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The need of the present is to develop environmentally safe alternative for effective nematode control. Several natural and synthetic derivatives have been found effective against M. incognita , Bose et al 2010, Attar et al 2011, Kaushik et al 2015, Caboni et al 2016, Yadav et al 2019. In the present study, the bioefficacy evaluation of most potent molecules, identified on the basis of in vitro results, is reported in pot cultured tomato cv.…”
mentioning
confidence: 73%
“…On the other hand, ferrocenyl chalcone synthesis and their biological evaluations were well studied. Yadav et al synthesized 16 ferrocenyl chalcone through using microwave in high yields and screened them for antifungal against Sclerotium rolfsii and Alternaria solani (Yadav et al, 2019). They have found that their chalcones showed good antifungal activity.…”
Section: Figure 1 Some Natural Compounds Containing Chalcone Unitmentioning
confidence: 99%